2011
DOI: 10.1248/bpb.34.408
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Localization of Ileal P-Glycoprotein Induced by Intestinal Ischemia/Reperfusion

Abstract: ATP binding cassette (ABC) transporters form one of the largest families of membrane transport proteins and are expressed in all organisms. They have been studied extensively and play a vital role in many cellular processes. ABC transporters are responsible for the multidrug resistance of cancer cells 1) but may also be capable of transporting several substrates such as metal ions, peptides, amino acids, sugars, and a large number of hydrophobic compounds and metabolites across the plasma membrane as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…6A and 6B) and P-gp protein expression in the ileal homogenate (data not shown) were not decreased. Takizawa et al (23) reported abnormal localization of P-gp in the ileal membrane during intestinal I/R. This finding suggests that abnormal localization of P-gp also occurs in our intestinal I/R-15 model rats.…”
Section: Discussionsupporting
confidence: 55%
“…6A and 6B) and P-gp protein expression in the ileal homogenate (data not shown) were not decreased. Takizawa et al (23) reported abnormal localization of P-gp in the ileal membrane during intestinal I/R. This finding suggests that abnormal localization of P-gp also occurs in our intestinal I/R-15 model rats.…”
Section: Discussionsupporting
confidence: 55%
“…We have already reported that changes in the function and expression of ileal P-gp, which is an important ATP-binding cassette transporter, by intestinal I/R. 11,12,20,21) Moreover, we reported AG significantly inhibited the decrease of ileal P-gp function to excrete P-gp substrate, rhodamine 123, into the ileal lumen and expression by intestinal I/R until 1 h after reperfusion. 13) These results showed that AG can inhibit intestinal I/R injury until 1 h after reperfusion.…”
Section: Discussionmentioning
confidence: 93%